A REVIEW ON ROLE OF PANCHAMABHUTA IN GARBHA UTPATTI - Prathima; Hadimane Sushmitha S (International Journal of Ayurveda and Pharma Research, 2020)
In present days of globalizations all are concentrated in finding basics of transformations or existence. The concept of Panchamahabhuta (five basic elements) has been scientifically explained in Ayurveda. Panchamahabhuta are important components of the body. It is the five basic constituents which exist in the universe and human beings; they are Akasha, Vayu, Agni, Jala and Prithvi. The union of Shukra (sperm) and Shonitha (ovum) and Atma (soul) in the Kukshi (uterus) is designated as Garbha (embryo). The five Mahabhuta (basic elements) play a important role in formation, development and maintenance of Garbha (embryo). The five elements refer to etheric, gaseous, radiant, fluid and solid states of matter. Mahabhutha plays an important role in Garbhautpatti (embryogenesis). It helps in separation and segregation of cell mass, nourishment, structural development etc. The present work is to study the concept of these five elements in embryogenesis.